Soviet Jews in World War II Fighting, Witnessing, Remembering - Estraikh, Gennady; Murav, Harriet (Borderlines, 2014)
This volume discusses the participation of Jews as soldiers, journalists, and propagandists in combating the Nazis during the Great Patriotic War-as the period between June 22, 1941, and May 9, 1945, was known in the Soviet Union. The essays included here examine both newly discovered and previously-neglected oral testimony, poetry, cinema, diaries, memoirs, newspapers, and archives. This is among the first books to combine the study of Russian and Yiddish materials, reflecting the nature of the Jewish Anti-Fascist Committee, which for the first time during the Soviet period included under the same institutional umbrella both Yiddish-language and Russian-language writers. This volume will be of use to scholars, teachers, students, and researchers working in Russian and Jewish history.